IT Audit of IT Service Provider Using COBIT 4.1 Framework: Case Study at PT. XYZ - Muhammad Malik Hakim (Fountain of Informatics Journal, 2017)
IT service providers often campaign for the importance of having a high level of IT maturity to its customers. However, not all IT companies have a high commitment to IT management within their own organisation. As a case study, this paper attempts to measure the IT maturity level of PT. XYZ that now is a growing IT services provider. Data collection is done by interview, document study, and direct field observation. The measurement of IT maturity level is conducted using 4 domains of COBIT 4.1 Framework, consists of Plan and Organize (PO), Deliver and Support (DS), Acquire and Implement (AI), and Monitor and Evaluate (ME). The result shows a value of 2.5 which indicates that IT maturity level is at level 2 (Repeatable but Intuitive) which means low enough for companies that should have a high awareness of IT governance and commitment. This study shows that the level of IT maturity in IT service provider is not always as high as its campaign.